Accumulation - Pokwatka, Aimee (G.P. Putman's Sons, 2026)
"A twisty, searing, conversation-starting novel about a filmmaker-turned-housewife who moves into her dream house and is forced to consider whether it's the house or herself that is haunted. When documentary filmmaker turned stay-at-home mom Tennessee Cherish moves into the the dream house her husband bought for her, a brighter future seems to be on the horizon. Even if her husband is frustratingly absent due to his new high-paying job. Even if their two young children begin acting out in strange ways. Even if she feels lonelier than ever. Distracted by the endless details that come with moving into a new town, a new house, and new schools, Tenn doesn't notice when odd things begin happening at home. The faucet that runs at all hours. The creepy doll that seems to show up in every room. The human tooth they found in the floorboards. As the kids' outbursts and the strange events start to escalate, the family finds themselves increasingly caught in loops, repeating everyday actions with dangerous - and then devastating - effects. Tenn realizes she must find the source of what is haunting her family, before it kills them all. Taut and twisty, scary and searing, Aimee Pokwatka's Accumulation lays bare the high price women pay for the promises of domesticity and motherhood, and the many ways in which families can be haunted"-- Provided by publisher.